2018
DOI: 10.3390/su10072347
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst or Barrier? The Influence of Place Attachment on Perceived Community Resilience in Tourism Destinations

Abstract: Abstract:The concept of resilience has recently received a substantial amount of attention in sustainable tourism research. Nevertheless, empirical studies on the factors that may influence the perceived resilience of community residents in tourism destinations remain lacking. A thorough analysis is needed to examine place attachment as a catalyst of or a barrier to community resilience in tourism destinations. Structural equation modeling was used to analyze the influence of place attachment on perceived resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 73 publications
(99 reference statements)
2
20
0
3
Order By: Relevance
“…Regarding disasters in tourism, some previous studies have estimated residents' resilience after the disasters and found that the residents considered the risk management of tourism (Guo et al, 2018;Nian et al, 2019). Nian et al (2019) focused on the relationship between crisis response and tourism community participation after the Wenchuan earthquake in China in 2008 and found that perception of benefit, community attachment, and community resilience had positive effects on crisis response and community participation.…”
Section: Residents' Attitude and Disastersmentioning
confidence: 99%
“…Regarding disasters in tourism, some previous studies have estimated residents' resilience after the disasters and found that the residents considered the risk management of tourism (Guo et al, 2018;Nian et al, 2019). Nian et al (2019) focused on the relationship between crisis response and tourism community participation after the Wenchuan earthquake in China in 2008 and found that perception of benefit, community attachment, and community resilience had positive effects on crisis response and community participation.…”
Section: Residents' Attitude and Disastersmentioning
confidence: 99%
“…Community members with strong attachments to their online community proactively provide valuable content [18], answer other members' questions [19], and increase the value of current community content [20]. It is especially critical for UGC service providers to lead and guide members toward a strong community attachment because the continuous acquisition of secure, high-quality content is an important core factor for an online site's survival, as well as success [21,22]. Therefore, UGC service providers should understand the mechanism and factors that affect community attachment as a means to retain members.…”
Section: Introductionmentioning
confidence: 99%
“…A sense of continuity with one’s place should be associated with self-efficacy, that is, a sense of belief in one’s own abilities to meet and manage changing circumstances. Many scholars have further studied the theoretical framework of local attachment and its role in urban disaster prevention and community emotion shaping [34,35,50]. A sense of community facilitates the involvement of individuals in community response following disasters and increases their access to, and utilization of, social support networks coping with a community stressor [51].…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…From the perspective of stakeholders of tourism destinations, the research on post-disaster community participation has become a hotspot. Many scholars have examined the factors influencing disaster prevention in the tourist community, including community resilience [29,30,31], community participation support [32,33], place attachment [34,35], community attachment [36,37], community livelihood [38], social capital [39], crisis response [40], and crisis management [4]. Research on tourist communities focuses on community engagement models, community empowerment, community involvement, community attachment, and so on [41,42], and mainly relies on the social exchange theory, local identity theory, and tourism life cycle theory [23,43,44,45].…”
Section: Introductionmentioning
confidence: 99%